Pendapatan Usahatani Padi Gogo Varietas Unggul Baru pada MK I di Provinsi Gorontalo - Rouf, Ari Abdul; Munawaroh, S; Moko, HD (Seminar Nasional Lahan Suboptimal, 2022)
Rouf AR, Munawaroh S, Moko HD.  2022. New superior varieties of dryland rice farming income at first dry season in Gorontalo Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 947-953. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the production factors that is limiting the fulfillment of rice in Indonesia is limited irrigated rice fields. On the other hand, Indonesia has a fairly large dry land but its use still requires the application of technology. The Agency for Agricultural Research and Development through BB Padi since 2017 has disseminated upland rice technology known as Larikan Gogo Super (Largo Super). This research aimed to determine the productivity and income of new superior upland rice based on upland arrays. In this study, the technology studied is the upland rice technology package (Largo Super). The experimental design used was a randomized block design with 6 treatments and 4 replications. The treatment of the study was upland rice varieties including Ponelo, Rindang 2, Inpago 8, Inpago 9, Inpago 11 and Inpago 12. The results of the study show that the upland array technology of Inpago 8 and 9 varieties has an RC Ratio value above 1, this means that the variety is feasible to cultivate because sales of upland rice can cover the costs of implementing upland rice array technology.